Association Between Interpregnancy Interval and Adverse Birth Outcomes in Women With a Previous Stillbirth: An International Cohort Study. Issue 9 (September 2019) - Regan, Annette K.; Gissler, Mika; Magnus, Maria C.; Haberg, Siri E.; Ball, Stephen; Malacova, Eva; Nassar, Natasha; Leonard, Helen; Pereira, Gavin
Abstract : (Abstracted from Lancet 2019;393:1527–1535) Interpregnancy interval (IPI; the length of time between pregnancies) is a risk factor for adverse outcomes in infants and their mothers. The World Health Organization recommends women wait at least 2 years after a live birth and 6 months after miscarriage or abortion before conceiving again, but there is no recommendation for the best IPI after stillbirth.